World Food Day 2015: Tadelle Dessie on the contributions of poultry to social protection - Dessie, Tadelle (International Livestock Research Institute, 2015)
Periscope interview with Tadelle Dessie, a researcher with the International Livestock Research Institute (ILRI) in Addis Ababa, Ethiopia, filmed for the World Food Day 2015.